Calcretes and travertines from the Palaeocene Itaboraí Basin as evidence of the early evolution of the Southeastern Brazil Continental Rift. Issue 1 (11th October 2020) - Adler, Paula Braga; De Ros, Luiz Fernando; Mansur, Kátia Leite; Ferrari, André Luiz; Fernandes, Luiz Alberto; Sial, Alcides Nóbrega
Abstract: The Itaboraí Basin, located in Rio de Janeiro state, is the smallest segment of the Southeastern Brazil Continental Rift, and the first to open, during the Palaeocene. Numerous studies focused on its fossiliferous content, but few systematically approached its depositional and diagenetic processes and products. A detailed description of the basal sedimentary deposits that remained after nearly fifty years of exploitation for cement production allowed an interpretation of the initial tectono‐sedimentary conditions responsible for the formation of the Basin. The macroscopic and petrographic description of outcrops and well core samples of the calcretes and travertines that correspond to the initial basin infill was integrated with stable isotope geochemistry. The calcretes were separated into different facies (powdery, nodular, massive, platy, laminated and brecciated), and classified according to morphogenetic stages. Their main microscopic features include nodules, contraction cracks, vadose pisoliths, rhizocretions, infiltrated clays, corroded grains, expanded micas and clay aggregates with bimasepic–plasmic microfabric. The travertines exhibit diverse forms of abiotic calcite crystal aggregates (plumose, lamellar to prismatic‐radial, spherulitic) and a minor proportion of microbial microcrystalline precipitates (bacterial shrubs). Tectonically active periods, characterized by intense fault movements associated with humid climate, promoted hydrothermal activity, formation of travertines and modification of the alluvial deposits and calcrete facies by ascending fluids. During periods of tectonic stability under arid to semi‐arid climate, the exposed alluvial and hydrothermal deposits were influenced by pedogenetic processes. Sulphide‐rich carbonate hydrothermal breccias occur in the main fault zone at the southern border. The characterization of extremely active pedogenetic and hydrothermal processes during opening and early evolution of the Itaboraí Basin is essential to the understanding of the initial evolution of the Southeastern Brazil Continental Rift. Additionally, some isotopic and petrographic similarities of the Itaboraí carbonates with the vast South Atlantic Aptian Pre‐Salt lacustrine deposits may offer an interesting contribution to the understanding of that important petroleum province.